Exploring the primary care experiences of adult patients with eating disorders: a qualitative analysis. Issue 1 (2nd January 2021) - Lazare, Kimberly; Mehak, Adrienne; Telner, Deanna
ABSTRACT: Eating disorders (EDs) are severe psychological conditions, often requiring specialized treatment. Patients with EDs generally first present in primary care before being referred to tertiary centres. Evidence suggests that family physicians do not identify most patients with clinical EDs. The objective of this study was to explore the primary care experiences of adult patients with EDs. Ten individual, semi-structured interviews with adult women with an ED were conducted. A qualitative descriptive approach was adopted using thematic analysis. The researchers identified codes, which were categorized into five major themes: 1) disparate patient experiences in primary care, 2) delayed diagnosis, 3) key family physician qualities for ED care, 4) individual and systemic barriers to recovery, and 5) patient needs in primary care. Most participants reported that their diagnosis was not timely, suggesting a need for improved screening and diagnostic procedures. Inconsistent treatment practices imply that family physicians would benefit from the development of standardized guidelines for ED diagnosis and treatment in primary care as well as additional training in ED care. Family physicians being empathic and nonjudgmental and facilitating access to resources are of particular importance to this patient population.